Тhe Influence of Loud and Silent Reading of Texts on Reading Comprehension in the Fourth Grade of Primary School - Ivana P. Stojkov (University of Belgrade, Teacher Education Faculty, 2018)
The aim of this paper is to describe the types of reading, the understanding of the text that has been read, and the view of the results of an empirical research about their connection, because the way in which students read has an influence on understanding of the content of the text. This paper analyzes knowing and using the basic types of reading - reading aloud and silent reading (inside voice), although within them we can differ explorative, logical, critical and interpretative reading. Precondition for interpretation of literature text is that the student understands what he reads, and it is important to measure the type of reading (by genre) because the results of learning will be more effective. This paper also shows the results of the pilot research about the influence of loud and silent reading on text understanding in the fourth grade of elementary school. The sample of research included 50 students of the primary school fourth graders in Belgrade. We presumed that the reading type influenced understanding of the read text if they read it silently. This is shown in the reference of literature teaching methodology, as well as in earlier researches. Having analysed and studied the results, we can conclude that there is no major difference between the read text and the type of reading (aloud, silent). However, the results of this research are different. Independently of the reading type and including other factors (speed of reading, reproductive and productive questions, individual student characteristics), the level of understanding is practically the same. We can conclude that no matter what type of reading is practiced, the level of understanding of the read text by the fourth grade students is the same. This research can be the starting point for the next determination of the influence of reading types on the read text that implies the development of the process of being literate and makes teaching of the mother tongue much better.